2016
DOI: 10.1002/art.39442
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Protein Tyrosine Phosphatase α–Mediated Enhancement of Rheumatoid Synovial Fibroblast Signaling and Promotion of Arthritis in Mice

Abstract: Objective During rheumatoid arthritis (RA), fibroblast-like synoviocytes (FLS) critically promote disease pathogenesis by aggressively invading the joint extracellular matrix. The focal adhesion kinase (FAK) signaling pathway is emerging as a contributor to RA FLS anomalous behavior. The receptor protein tyrosine phosphatase α (RPTPα), encoded by the PTPRA gene, is a key promoter of FAK signaling. Here we investigated whether RPTPα mediates FLS aggressiveness and RA pathogenesis. Methods Through RPTPα knockd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 49 publications
2
28
0
Order By: Relevance
“…FAK phosphorylation levels are increased in RA synovial lining cells compared with normal synovial tissue (39), and DNA methylation abnormalities were identified within the FAK pathway in RA FLS (8). Additionally, we recently reported that another tyrosine phosphatase that promotes FAK activation — receptor PTP-α — also mediates the aggressiveness of RA FLS and promotes arthritis in mice (40). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…FAK phosphorylation levels are increased in RA synovial lining cells compared with normal synovial tissue (39), and DNA methylation abnormalities were identified within the FAK pathway in RA FLS (8). Additionally, we recently reported that another tyrosine phosphatase that promotes FAK activation — receptor PTP-α — also mediates the aggressiveness of RA FLS and promotes arthritis in mice (40). …”
Section: Resultsmentioning
confidence: 99%
“…RA FLS migration was assessed in Transwell chambers (Corning) as previously described (12, 40). Each experiment included 3 membranes per sample, and 4 fields were analyzed per membrane.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously surveyed the expression of protein tyrosine phosphatases (PTPs) in FLS from patients with RA (RA FLS) and reported that PTPσ, PTPκ and PTPα promote the aggressiveness of RA FLS 5–7. In the same survey, non-receptor protein tyrosine phosphatase 14 (PTPN14, also known as PEZ) was found to be among the most highly expressed PTPs in RA FLS 8…”
Section: Introductionmentioning
confidence: 99%